Assessment of functional recovery after cranioplasty - Madhavan, Girish K.; Issac, Philip; Kunjan, Balakrishnan P.; Jose, Tom; John, Ajax (International Surgery Journal, 2021)
Background: Cranioplasty is done after decompressive craniectomy surgeries either for cosmetic reasons or to afford protection against the development of the syndrome of the trephined which is deterioration after cranial decompression procedures. The aim of the study was to study functional recovery after cranioplasty based on improvement of Barthel activities of daily living (ADL) score. Methods: This was a prospective study done over 6 months period, December 2020 to May 2021. The functional recovery following cranioplasty was assessed based on improvement in Barthel ADL score. Pre-operative and post-operative Barthel ADL score after 3 months after cranioplasty of patients are found out. The change in Barthel score is analyzed and significance found out using paired t test. Results: In this study, 62 patients were included. 42 patients had improvement of ADL score. 14 patients had no change and 6 patients had worsening of score. After cranioplasty, ADL score has improved and it was statistically significant (p<0.001). Also, patients with low level of dependency (level 1, 2 and 3) have decreased in number and patients with higher levels of dependency (level 4 and 5) have increased in number after the surgery, suggesting that there is shift of patients from lower level of dependency to higher levels. Conclusions: Cranioplasty seems to offer patients clear benefits in terms of neurological improvement in many cognitive domains as well as in quality of life. Hence, cranioplasty advocated for functional/neurological recovery rather than cosmetic reasons.